Effect of Copper on Microstructure and Corrosion Resistance of Hot Rolled 301 Stainless Steel - Na Li; Hangxin Yan; Xuyuan Wang; Lei Xia; Yuchuan Zhu; Yan Li; Zhengyi Jiang (Metals, 2023)
The effect of copper (Cu) on hot-rolled 301 austenitic stainless steel (ASS) was studied by observing the microstructures and testing the electrochemical corrosion resistance properties. The results showed that, with the increase in Cu content, the size of shear zones in 301 ASS decreased, and the number increased, which increased the uniformity of the microstructure macroscopically. The presence of Cu decreased the stacking fault energy of 301 ASS at elevated temperatures. Meanwhile, the amount of chromium (Cr) carbides decreased gradually with the increase in Cu content, which implies that the solid solution of Cu in hot-rolled 301 stainless steel promotes the solid solution of Cr and C in the steel, which is conducive to the formation of Cr-rich passivation films. As a result, the corrosion resistance of hot rolled Cu-bearing 301 stainless steel is improved, with both lower corrosion current density (Icorr) and passivation current (Ipass), and more positive corrosion potentials (Ecorr) and passivation potential (Ep), even though it does not show a higher pitting resistance. As Cu content in the steel was increased from 0.4% to 1.1%, the corrosion resistance was not further improved.